Non-Invasive Diagnostic of Renal Allograft Rejection Via Urine Metabolites Using NMR-spectroscopy. (July 2018) - Banas, Miriam; Neumann, Sindy; Pagel, Philipp; Schiffer, Eric; Chittka, Dominik; Banas, Bernhard
Abstract : Introduction and Background: Post-transplant surveillance for acute rejection is typically based on regular monitoring of serum creatinine levels and consecutive biopsies upon functional renal impairment. Attempts have been made to develop non-invasive tests based on urinary markers to detect acute rejection. Probably due to high costs of analysis and lack of platform standardization, none of the tests has been established in the clinical routine so far. Recently, we explored an approach to detect rejection by a urinary metabolite network using inexpensive and standardized nuclear magnetic resonance spectroscopy (NMR). Our aim was to validate the test in a first prospective study. Methods: Within the prospective Umbrella study 2, 479 urine specimens from 109 consecutive kidney-graft recipients from day 1 through month 12 after transplantation were collected at University Hospital Regensburg. The specimens were analyzed using NMR and the results were compared to the allograft-rejection status according to the biopsy results. Results: The metabolic constellation was able to detect acute cellular allograft rejection during outpatient phase (≥ day 15 after transplantation, area under the curve (AUC) 0.75, [95% confidence interval (CI) 0.68 to 0.83], P<0.001). A combination of the test with serum creatinine based estimated glomerular filtration rate (eGFR) significantly improved the overall performance (AUC 0.84). In order to investigate possible drug interference effects on the metabolite network, we analyzed the score distribution in all available control urine samples from patients that never showed rejection episodes. In control urine samples only glucose infusions or antihistamine medication caused potential drug interferences. None of the other medications induced relevant increases in the score. Conclusions: In conclusion, the metabolite constellation in combination with eGFR appears to be a reliable non-invasive test to support post-transplant outpatient biopsy decision making. To confirm the results from the previous Umbrella study we have now started a European multicenter study.